Roles of Integrating Information Communication Technology (ICT) in Teaching Speaking at the First Semester of English Students oF FKIP UIR - Andi Idayani; Betty Sailun (J-SHMIC : Journal of English for Academic, 2017)
Speaking skill is an important part of the curriculum in language teaching, this makes it an important for students to be able to speak English. However, the goal of teaching speaking should improve students’ communicative skills as a way to help students express themselves and learn how to follow the social and cultural rules appropriate in each communication circumstance.Hence, Information Communication Technology (ICT) can be used by the English teacher to enhance students’ English Proficiency, especially speaking skill. Thus, the present study aims at investigating the role of Information Communication Technology (ICT) in speaking class at the first semester of English Students of FKIP UIR which consists of 42 students as sample of this research. The researchers used descriptive method and worked by using questionnaires as an instrument for collecting data. The researchers have found that the use of Information Communication Technology (ICT) increases students’ motivation and their speaking performances. It also has great impact on students learning’s effectiveness. In general, students prefered group work activities, free discussion, role play, or students’ presentation. A large number of students declared that their lecturer used technology while teaching speaking. They claimed that using ICThas beneficial and helpful to speak the language. Finally, most students affirmed that the use of ICT developed their speaking skill, increased their knowledge, and creativity. Concerning their attitudes towards their preferable kind of technology that can be used in teaching, some prefer to use laptop/notebook and projector while others enjoyed watching videos.